CHARACTER EDUCATION INVESTMENT IN SD/MI - muhamad afandi (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
Character education in SD/MI is a process guide and inculcate noble values into the students SD/MI in order to be implemented in the behavior, toward Allah SWT, itself, others, and the environment as a whole. The Values of the character education were developed from four sources, namely : religion, Pancasila, culture, and national education goals. The implementation of the character education in SD/MI can be done through three ways, namely : to integrate with the subjects and local content, integrating through of self-development activities, and integrating through of the cultural school/ madrasah activity.